Identification of a novel non-sense mutation in TBX5 gene in pediatric patients with congenital heart defects - Mehri Khatami; Mohammad Mehdi Heidari; Fatemeh Kazeminasab; Razieh Zare Bidaki (Journal of Cardiovascular and Thoracic Research, 2018)
Introduction: Congenital heart diseases (CHDs) are structural cardiovascular malformations that arise from abnormal development of the heart during the prenatal life. Mutations in the TBX5 gene, encoding T-box transcription factor, are a major cause of CHD. To evaluate the TBX5 mutations in hotspot exons in sporadic pediatric patients with CHD phenotypes, analytical case/control study performed in an Iranian cohort of unrelated patients with clinical diagnosis of congenital heart malformations. Methods: We investigated TBX5 coding exons 4, 5, 6 and 7 in 95 sporadic patients with CHD phenotypes and compared to 82 healthy controls using PCR-SSCP and DNA sequencing approaches. Results: We report here on a novel and heterozygote Non-sense mutation in exon 5 of TBX5, E128X (G14742T), in two Iranian children. This mutation locates inside the T-box and both of pediatric patients carrying this novel mutation suffer from severe heart malformations. The G14742T mutation leads to the substitution of glutamic acid (E) by stop codon (X) at residue 128, an evolutionarily conserved position in T-box as well as in other species. The non-sense mutation of E128X was predicted to be pathogenic by Mutation Taster and Polyphen software programs. Conclusion: TBX5 E128X mutation results in a translational premature stop. This type of mutation results in a shortened protein that may function improperly and which cannot bind to other transcription factors; therefore, haploinsufficiency of TBX5 protein is presumably causing the severe cardiac malformations in these patients.